Service Sector Employee Insights Into the Future of Work and Technological Disruption - Haar, J; Brougham, D; Tootell, B (ER Publishing Ltd., 2019)
Recently there has been significant attention given to the fourth industrial revolution and its impact on employment. The present study aims to provide employee insights into their perceptions of the future of work, specifically around their job and career. These insights are important, as the respondents show how they plan to adapt (or more importantly, not plan or not adapt) to new jobs and careers in a rapidly changing world. Based on insights from 60 employees, which were collected online, the key findings suggest that people in the same line of work have varying degrees of knowledge and opinions about automation and how it may impact on their jobs. In addition, many employees are generally optimistic about the future of work and their long-term careers, with them acknowledging potential job changes around automation, but with a strong belief their type of work will remain. These are important findings when we consider how people plan their careers in the face of automation.
Keywords: Future of Work; Career Planning; Robotics; Artificial-Intelligence; Technology